Avaliação da microbiota lática cultivável de leite bovino e queijo coalho produzidos no Rio Grande do Norte - Souza, Lara Barbosa de (2015)
Milk and dairy products are of high nutritional value foods. And thus are part of the brazilian population diet in a wide age range. Due to its composition, these foods are a great way for development of micro-organism. The consumer interest in healthier foods increases the search for new conservation methods, for preserving the organoleptic characteristics of the food and contribute to their quality. Knowledge of the microbial population the milk and derivatives assists in the characterization of the hygiene conditions of the raw materials and derivatives production processes. It also provides a tool for the studying the biotechnological potential of lactic acid bacteria (LAB) naturally present in these foods. Which are directly linked to the formation of lactic acid, contributing to the coagulation of the milk. These bacteria are cited as the main factor capable of inhibiting the growth of pathogenic and spoilage micro-organisms. In this context, the objective was to evaluate the microbial rennet milk and cheese produced in the semiarid region of Brazil. Were analyzed 23 samples, 12 raw milk and 11 cheese curd, submitted will microbiological analyzes to count mesophilics bacteria, Staphylococcus spp. count, most probable number of total and thermotolerant coliforms, isolation and characterization of lactic acid bacteria and even front antagonism test to Staphylococcus aureus ATCC 25923 and Eschechia coli ATCC 25922. Only one sample showed reduced bacterial counts, for all analyzed microorganisms. We obtained 56 isolates of LAB, of which 29 (51.78%) were derived from milk samples and 27 (48.22%) of curd cheese samples. Of the total, 36 (64.3%) isolates of lactic acid bacteria (LAB) have demonstrated antagonistic activity against the indicators microorganisms. The greatest inhibitory effect was observed for isolates obtained from milk samples for E. coli. Strains of LAB showed inhibitory effect compared to the studied micro-organisms, showing their technological potential and their possible use as biopreservatives in food, contributing to the improvement of product quality and reducing of unwanted microbiota